INTERACTIVE MOBILE LEARNING GAMES ON BUGS AND HYGIENE FOR EARLY EDUCATION - Izah Shahirah, Mohamad (Universiti Malaysia Sarawak (UNIMAS), 2019)
Hygiene is practices in maintaining health and prevent disease. Most of the children are exposed with bug or bacteria either at home or school. Hence, they should expose with the awareness of taking care of their cleanliness. As the technology era is growing, interactive learning through mobile game application is suitable and help to attract children interest in learning something new. This mobile game application can help the parents or teachers to expose about the good personal hygiene to children. It is also knowledge the children about the bug that might infect them if they do not apply cleanliness in their daily life.